Strengthening Individual Teacher-Child Relationships: An Intervention Study Among Student Teachers in Special Education - Koenen, Anne-Katrien; Borremans, Liedewij Frieke Nel; De Vroey, Annet; Kelchtermans, Geert; Spilt, Jantine Liedewij (Frontiers in Education, 2021)
Relationships with children with special educational needs can be emotionally challenging for teachers and conflicts may negatively impact both children and teachers. Beginning teachers in particular may struggle with negative teacher-child relationships and the emotions these invoke. A first step in coping with relationship difficulties with specific children is increasing the teacher’s awareness and understanding of relational themes and emotions in the relationship with that specific child. Therefore, this multiple case intervention study examined the effects of LLInC (Leerkracht Leerling Interactie Coaching in Dutch, or: Teacher Student Interaction Coaching) in a sample of six student teachers in their final internship. LLInC is a relationship-focused coaching program using narrative interview techniques to facilitate in-depth reflection on teacher-child relationships. The intervention aims to foster teachers’ awareness of (negative) internalized emotions and beliefs in order to improve closeness and positive affect, and to reduce conflict and negative affect in teacher-child relationships. Participants repeatedly reported on their perceptions of the teacher-child relationship and on emotions in relation to a specific child before and after the LLInC intervention, which consisted of two one-on-one sessions with a coach. Visual between- and within-phases analyses revealed differential intervention effects across teachers on the development of teacher-child relationship quality and relationship emotions. For all teachers, except for one, positive effects were found on feelings of joy and perceptions of closeness. Preventive effects (i.e., stopping downward trends) were more often observed for competence-based and relationship-based emotions and perceptions (competence, commitment, closeness) than for basic emotions (joy, anger, worry). Although further research is needed, the results highlight the potential of LLInC in influencing pre-service teachers’ child-specific emotions and relationship perceptions. Directions for future research and implications for teacher education are discussed.